Field Guide to Frogs of Western Australia - Tyler, M.J (Western Australian Museum, 2013)
Western Australia is home to more than one third of the known frog species in Australia and new ones are still being discovered. This guide presents up to date information on all species, including their distribution and habitat - including the cane toad, which has just arrived in the state. The book also features extensive colour photographs and location maps to assist identification